A Comparison of the Effectiveness of Mindfulness-Based Stress Reduction and Acceptance and Commitment Therapy on Sexual Dysfunction and Self-Care in Women with Type 2 Diabetes - Dehghanipour Mojarad, Neda; Kakavand, Alireza; Keshavarz, Somayeh; Tahmouresi, Niloufar (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study aimed to compare the effectiveness of two psychological interventions—Mindfulness-Based Stress Reduction (MBSR) and Acceptance and Commitment Therapy (ACT)—on sexual dysfunction and self-care behaviors in women with type 2 diabetes. Methods and Materials: This study was conducted using a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of all women with type 2 diabetes who referred to the National Diabetic Patients Support Charity Association in Tehran during the period from September to November 2024. A sample of 45 participants was selected through convenience sampling and randomly assigned to three groups: mindfulness, acceptance and commitment therapy, and control. Data collection instruments included the Diabetes Self-Care Questionnaire and the Female Sexual Function Index (FSFI). The experimental groups participated in eight 90-minute group intervention sessions. Data were analyzed using repeated measures analysis of variance. Findings: The results indicated that both interventions significantly improved sexual function and enhanced self-care behaviors compared with the control group (p < .01). Furthermore, significant differences were observed between the two interventions, such that the mindfulness-based intervention exerted a greater effect on improving self-care and sexual function compared with acceptance and commitment therapy. Conclusion: The findings suggest that psychological interventions—particularly mindfulness-based stress reduction—can effectively improve psycho-behavioral outcomes associated with type 2 diabetes in women, and their integration into treatment programs for chronic patients is strongly recommended.